Morphometric correlation between Apis mellifera morphotypes (Hymenoptera) and Varroa destructor (Acari) from Uruguay - Giménez Martínez, Pablo (2017)
Uruguay is characterized by having an Africanization gradient in its honey bee (Apis mellifera) populations from areas bordering Brazil to the most remote locations. Morphological differences have also been found among Varroa destructor populations from different regions. A possible explanation for these morphological changes in mites could be explained by morphological correlations in the host/parasite A. mellifera/V. destructor system. The objective of the present study was to identify A. mellifera ecotypes in Uruguay and their correlation with V. destructor populations, using geometric morphometrics analysis. The hypothesis states that there is an Africanization gradient of A. mellifera in the north-southeastern direction in Uruguay that correlates with morphological variations in V. destructor populations. A morphometrics analysis of six honey bee populations and their respective phoretic mites was carried out by sampling zones that show the gradient in the Uruguayan region. The main results obtained were a morphometric correlation between honey bees and mites. The use of landmarks could be adjusted for the intraspecific differentiation of V. destructor populations, which had not been considered previously. These studies are of major importance to further understand the parasitism caused by V. destructor in honey bees.